Antiherpes simplex virus activities of extracts from Glycosmis Pentaphylla (RETZ.)DC., Ipomoea Maxima (LINN.F.) Don, and Willughbeia Edulis ROXB - Paisan Piboonrattanakul (Chulalongkorn University, 2012)
Thesis (M.Sc. in Pharm)--Chulalongkorn University, 2004